Economic development and industrial concentration: An inverted U-curve - Karsten Junius (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
This paper sets up an economic geography model to show the endogenous forces that determine the degree of industry concentration in the course of economic development. The model includes centrifugal forces, such as home market effects and access to intermediate suppliers, and centripetal forces, such as demand pull of dispersed resources and congestion effects. Economic development increases the size of the industrial sector in terms of employment relative to the size of the agricultural sector. The relative strength of centripetal and centrifugal forces depends on the initial industry distribution, transport costs, and the level of economic development. These parameters lead to an inverted U-curve pattern of industry concentration, which is first increasing and then decreasing with per capita GDP. The model shows why the curve is more pronounced in newly industrializing economies than in industrialized countries, thereby explaining exceptionally high primacy ratios in today's developing countries.
Keywords: R11; R12; 330; Economic Geography; Agglomeration; Industrialization; Development; Industriestandort; Regionale Konzentration; Agglomerationseffekt; Standorttheorie; Entwicklungsstufe; Theorie; Entwicklungsländer; Industriestaaten